Energy harvesting from pavements - Dawson, Andrew; Mallick, Rajib; Hernandez, Alvaro García; Dehdezi, Pejman Keikhaei (Springer, 2014)
Against a background of the immense solar radiation incident with available pavement surfaces, the opportunity for energy to be harvested from pavements is investigated. While the emphasis is on the harvesting of solar-derived heat energy, some attention is also paid to the collection of energy derived from displacement of the pavement by traffic and to solar energy converted directly to electricity via photovoltaic systems embedded in pavements. Basic theory of heat collection is covered along with a discussion of the relevant thermal properties of pavement materials that affect heat transmission and storage in a pavement. Available technologies for pavement energy harvesting are reviewed and some of their advantages and limitations reviewed. The chapter continues with some descriptions of the ways in which the harvested energy can be stored and then used before ending with sections on evaporative cooling of pavements and system evaluation.